Design of an H-type vertical axis wind turbine - Lee, Xian Jing. (2012)
In recent years, there is an increasing interest in vertical axis wind turbines (VAWT) due to its advantages over the prevalent horizontal axis wind turbines. More experiments and research need to be carried out VAWT before it can be a commercial success. Currently, there are various type of VAWT invented. They are mainly lift based and drag based vertical axis wind turbine.